PROGRAM DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN LABUHABATU UTARA - Simon Beni Arianto Purba; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
PAD (Local Own-Source Revenue) Enhancement so depends on potention owned by an area. One of the attempt that can be used to increase PAD is by increasing local tax excavation and area retribution of Government City/Regency as optimal as possible. Therefore, it requires the efforts to increase Local Own-Source Revenue through establishment of local finance development management enhancement program. To know intensification and ekstensification program conducted by Department of Finance Management Income and Local Asset of North Labuhanbatu Regency in increasng PAD. Where The regency of North Labuhanbatu had been able to increase PAD in every year since 2008 this area was raised.This research was conducted in North Labuhanbatu Regency, precisely Department of Finance Management Income and Local Asset, where the informan of this research was the Leader of Department of Finance Management Income and Local Asset, also Head of Income Division Department of Finance Management Income and Local Asset. Sampling method by using purposive sampling. In data collection was used field reasearch method, interview, observation, study of literature and documentation. Gathered data then analyzed by using qualitative descriptive analysis.After the research conducted, found that the implementation of Department of Finance Management Income and Local Asset program in increasing PAD North Labuhanbatu Regency had done well and had been able to increase PAD of North Labuhanbatu Regency every year, but it was not maximal yet due to the existence of troubles faced in running the program i.e., Human Resources, People Awareness, and Infrastructure.Key words : Program, PAD Enhancement.